Recognition of the Protein Kinase AVRPPHB SUSCEPTIBLE1 by the Disease Resistance Protein RESISTANCE TO PSEUDOMONAS SYRINGAE5 Is Dependent on S-Acylation and an Exposed Loop in AVRPPHB SUSCEPTIBLE1 . Issue 1 (13th November 2013) - Qi, Dong; Dubiella, Ullrich; Kim, Sang Hee; Sloss, D. Isaiah; Dowen, Robert H.; Dixon, Jack E.; Innes, Roger W.
Abstract : A nucleotide-binding protein distinguishes among closely related protein kinases based on plasma membrane localization and an exposed loop in the C-terminal third of the kinase domain . Abstract: The recognition of pathogen effector proteins by plants is typically mediated by intracellular receptors belonging to the nucleotide-binding leucine-rich repeat (NLR ) family. NLR proteins often detect pathogen effector proteins indirectly by detecting modification of their targets. How NLR proteins detect such modifications is poorly understood. To address these questions, we have been investigating the Arabidopsis ( Arabidopsis thaliana ) NLR protein RESISTANCE TO PSEUDOMONAS SYRINGAE5 (RPS5), which detects the Pseudomonas syringae effector protein Avirulence protein Pseudomonas phaseolicolaB (AvrPphB). AvrPphB is a cysteine protease that specifically targets a subfamily of receptor-like cytoplasmic kinases, including the Arabidopsis protein kinase AVRPPHB Susceptible1 (PBS1). RPS5 is activated by the cleavage of PBS1 at the apex of its activation loop. Here, we show that RPS5 activation requires that PBS1 be localized to the plasma membrane and that plasma membrane localization of PBS1 is mediated by amino-terminal S -acylation. We also describe the development of a high-throughput screen for mutations in PBS1 that block RPS5 activation, which uncovered four new pbs1 alleles, two of which blocked cleavage by AvrPphB. Lastly, we show that RPS5 distinguishes among closely related kinases by the amino acid sequence (SEMPH) within an exposed loop in the C-terminal one-third of PBS1. The SEMPH loop is located on the opposite side of PBS1 from the AvrPphB cleavage site, suggesting that RPS5 associates with the SEMPH loop while leaving the AvrPphB cleavage site exposed. These findings provide support for a model of NLR activation in which NLR proteins form a preactivation complex with effector targets and then sense a conformational change in the target induced by effector modification.